Monitoring dengue outbreaks during COVID-19 crisis in dengue endemic countries - Miah, Asaduzzaman (International Journal of Infection Control, 2020)
During the COVID-19 crisis, dengue cases have been increased especially in dengue endemic countries. Currently we are fighting against COVID-19, the situation may be more difficult to manage if dengue outbreak is further added. During COVID-19 crisis, there is a possibility to occur co-infection of corona and dengue virus in these dengue endemic countries as both the viruses are co-existing. Altogether, further outbreak of dengue, viral co-infection and concurrent outbreak may pose new challenges in the dengue endemic countries specially for the health professionals.